Risk of cytomegalovirus transmission by blood products after solid organ transplantation. Issue 2 (3rd April 2019) - Jebakumar, Deborah; Bryant, Patti; Linz, Walter
Abstract: Cytomegalovirus (CMV) infection and CMV disease are significant contributors to increased morbidity, mortality, and cost for immunocompromised solid organ transplant recipients. Although the most significant risk for CMV transmission is the CMV serological status of the transplant donor and recipient, exposure to blood products is another potential risk factor. Before the era of leukocyte reduction, CMV seronegative products were issued to reduce the risk of CMV transmission, thus rendering the products CMV safe. This approach requires maintenance of two inventories of blood products and continuous donor testing. Leukocyte-reduced cellular transfusion products are also considered CMV safe and are essentially universally available. To minimize the risk of CMV infection in transplant recipients, strategies include use of seronegative blood products or prestorage leukocyte reduction. However, no recent randomized prospective controlled trial directly compares the two CMV safety approaches for transplant recipients. Hence, current policy relies on historic trials and more recent observational studies. As a consequence, though generally considered equivalent approaches, preferred practice varies between centers. This review provides guidance to inform an acceptable practice approach.